Performance Analysis of SM-MISO with Q-CSIT in Wireless Sensor Network - Subuh Pramono; Muhammad Ibrahim; Feri Adriyanto; Alfin Hikmaturokhman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
In this paper, we investigate the role of Q-CSIT in SM-MISO for wireless sensor networks system. The SN are connected to the CH, it is modeled as a MISO system. Spatial modulation has an advantage over a conventional MIMO system which does not require multiple radio frequency chains as many as the number of transmit antennas. The Q-CSIT is aimed to estimate the faded wireless channel with a limited/finite number of bits. The finite number of feedback bits trigger the SN adapt automatically its AMC modes. Adaptation of the AMC modes causes a changing of transmit power and transmission rate, these changes will make a better probability of error. The numerical results show that bigger the number of feedback bits yields better SER. Furthermore, lower spatial correlation generates a better probability of error. The last, quality of wireless channel that is stated in SNR also dominantly influences the performance of SM – MISO system.